2016
DOI: 10.3748/wjg.v22.i21.5096
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipokines might predict liver histology findings in non-alcoholic fatty liver disease

Abstract: Certain adipokines may determine the severity of NAFLD histology accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 26 publications
4
51
0
6
Order By: Relevance
“…Among them, the strongest association was with the grade of steatosis and then with portal information [ 68 ] Finally, in a recent evaluation of plasma biomarkers in a large well characterized biopsy proven NAFLD population ( n =648) by the NASH Clinical Research Network, resistin levels were similar between patients with a definite diagnosis of NASH vs borderline cases and healthy subjects, but were higher in patients with fibrosis stages 2 to 4 versus 0 to 1 (odds ratio, 1.12) [ 69 ]. These findings confirm previous results from smaller observational studies, that reported higher resistin levels in patients with histology proven NAFLD and advanced fibrosis [ 70 ].…”
Section: Resistinsupporting
confidence: 92%
“…Among them, the strongest association was with the grade of steatosis and then with portal information [ 68 ] Finally, in a recent evaluation of plasma biomarkers in a large well characterized biopsy proven NAFLD population ( n =648) by the NASH Clinical Research Network, resistin levels were similar between patients with a definite diagnosis of NASH vs borderline cases and healthy subjects, but were higher in patients with fibrosis stages 2 to 4 versus 0 to 1 (odds ratio, 1.12) [ 69 ]. These findings confirm previous results from smaller observational studies, that reported higher resistin levels in patients with histology proven NAFLD and advanced fibrosis [ 70 ].…”
Section: Resistinsupporting
confidence: 92%
“…In this study, the authors studied biomarkers in 648 histologically evaluated NAFLD patients demonstrating that fibrosis was associated with increased serum levels of resistin, IL-8, monocyte chemoattractant protein 1, soluble IL-1 receptor type and TNFα. Similar increased levels and an association with fibrosis were observed in another recent study suggesting that resistin may probably reflect a pro-inflammatory profibrogenic adipokine in NAFLD [ 88 ]. In contrast to mice, monocytes/macrophages are considered as the major source for resistin which may point towards a different biology in rodents and humans.…”
Section: Other Adipokinessupporting
confidence: 82%
“…Similar heterogenicity exists regarding the role of resistin in the pathogenesis of IR in PCOS (99,100). In patients with NAFLD, serum resistin levels correlate with the severity of steatosis, inflammation and fibrosis (95,101,102).…”
Section: Molecular Basis Including Endocrine Disruptorsmentioning
confidence: 98%